Corporate social responsibility and supply agreements in the private sector: Decreasing land and climate pressures - Kissinger, Gabrielle (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Corporate social responsibility (CSR) and supply agreements in the agricultural sector have a significant role to play to promote agricultural climate change mitigation and decrease pressure on the earth’s land and climate. Private sector engagement can also promote food security and positively affect the livelihoods of smallholder agricultural producers in developing countries. Based on a comprehensive literature survey and 15 interviews with key organizations, companies and financiers or lenders, this report investigates: current private sector climate change mitigation activities in agriculture and food production, highlighting current innovations affecting production and supply chains of key commodities; explores how CSR and supply chain commitments can improve their contribution to reductions in agricultural GHG emissions; and surveys the role of governments, finance and investment in promoting sustainability in the agricultural sector. Key findings identify a strong need for harmonization among product standards, certification and by commodity roundtables, and the need to mainstream sustainability criteria in agricultural finance and lending activities.